2019
DOI: 10.1186/s40425-019-0670-5
|View full text |Cite
|
Sign up to set email alerts
|

miR-34a as hub of T cell regulation networks

Abstract: Background Micro(mi)RNAs are increasingly recognized as central regulators of immune cell function. While it has been predicted that miRNAs have multiple targets, the majority of these predictions still await experimental confirmation. Here, miR-34a, a well-known tumor suppressor, is analyzed for targeting genes involved in immune system processes of leucocytes. Methods Using an in-silico approach, we combined miRNA target prediction with Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 50 publications
(57 reference statements)
2
30
0
Order By: Relevance
“…In search for a pathway to relate sustained NLRP3 inflammasome activation in aging we found a microRNA that has Pyrin-only protein 1 (POP1) as its target ( 33 ). This miR-34-5p is found to be increased in skeletal muscle and in serum-derived extracellular vesicles in an experimental model and considered as an “inflammiR” ( 34 ).…”
Section: Scenarios Of Covid-19 Immune Responsementioning
confidence: 99%
“…In search for a pathway to relate sustained NLRP3 inflammasome activation in aging we found a microRNA that has Pyrin-only protein 1 (POP1) as its target ( 33 ). This miR-34-5p is found to be increased in skeletal muscle and in serum-derived extracellular vesicles in an experimental model and considered as an “inflammiR” ( 34 ).…”
Section: Scenarios Of Covid-19 Immune Responsementioning
confidence: 99%
“…However, other in vitro experiments showed that miR-34a restoration can induce cell-cycle arrest and apoptosis [211]. In addition, miR-34a targets NOTCH1, E2F1 and B-MYB, which promote CLL cell proliferation [212], regulates the NF-κβ signaling in T-cells [213] and has a key role in the immune system response in cancer [214]. Thus therapeutic strategy involving the administration of miR-34a mimics in CLL may warrant further studies.…”
Section: Role Of Non-coding Rnas In Targeted and Immunotherapeutic Stmentioning
confidence: 99%
“…Treatment with a miR-34a inhibitor attenuates p53-mediated apoptosis in response to genotoxic stress, whereas the ectopic expression of miR-34a causes a signi cant reprogramming of gene expression and induces apoptosis and cell cycle arrest (23). miR-34a has been shown to directly target the 3′ UTRs of numerous mRNAs with roles in oncogenesis beyond p53, including Bcl-2, PIK3R2, c-Myc, SIRT1, VAMP2, IKBKE, MYH9, KLRK1, CD11A, SDK4-6, Notch1, TRAFD1, and CCR1 (23)(24)(25)(26)(27), which may contribute to its tumor-suppressive function.…”
Section: Introductionmentioning
confidence: 99%